CUMULUL INFRACŢIUNILOR DE CONTRABANDĂ ŞI DE ESCHIVARE DE LA ACHITAREA PLĂŢILOR VAMALE, PREVĂZUTE DE LEGISLAŢIA PENALĂ A REPUBLICII MOLDOVA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2008)
The fulfillment of the obligatory functions of the law-enforcement authorities without correlation with the other state authorities and especially with the non-governmental organizations and formations is practically impossible. The correlation between the law-enforcement authorities and the non-governmental organizations needs to be carried out on some principles and to be based on its specific particularities, which determine a whole range of actions, characterizing, on one hand, the law-enforcement authorities and, on the other hand, the non-governmental organizations, providing the support to the law-enforcement authorities on protection of the public order from criminal attempts by the offenders. Namely on the notion of „cooperation”, principles, categories, methods and ways.